Planktonic food web structure at SSTF and PF in the Indian sector of the Southern Ocean during austral summer 2011. Issue 1 (1st January 2018) - Pillai, H.U.K.; Anilkumar, N.; Achuthankutty, C.T.; Mendes, C.R.; Sabu, P.; Jayalakshmi, K.V.; Asha Devi, C.R.; Dessai, Deepti; George, Jenson; Pavithran, Sini; Hari Devi, C.K.; Tripathy, S.C.; et al.
ABSTRACT: This study aims to describe the planktonic food web structure with respect to phytoplankton biomass (chlorophyll a ) and prevailing environmental conditions at the South Subtropical Front (SSTF) and the Polar Front (PF) in the Indian sector of the Southern Ocean. Sampling was carried out at each front for 72 hrs, at 6-hr intervals, during the austral summer 2011. Considerable variations were observed in the hydrography between these two fronts. A strong temperature minimum layer was observed at the PF. Although the surface primary production and chlorophyll a values showed similar trends at both the fronts, the water column values of these parameters showed major disparities. The phytoplankton composition also revealed marked difference between the fronts. A deep chlorophyll maximum concordant with the upper limit of the temperature minimum layer was prominent at the PF. The microzooplankton abundance at the SSTF was twice as high as at the PF. The mesozooplankton biovolume and population density also showed considerable variations between these fronts. Noticeable diel variations were observed in the surface mesozooplankton biovolumes at both the fronts and the copepod Pleuromamma gracilis showed active diel vertical migration at SSTF. Both the grazing and senescence indices showed significant variations between these fronts, suggesting a disparity in the ecological efficiency of the two regions. The variability observed in the plankton community structure with respect to the hydrography and the biological components measured suggests that a multivorous food web at the SSTF and a conventional food web at the PF prevailed during the period of study.